Safety and security perception in shared autonomous shuttles: a user-centred evaluation of interface design and passenger behaviour - Bolzmacher, Christian; Panëels, Sabrina; Louison, Céphise; Hidalgo, Carlos; Marcano, Mauricio; Diaz, Sergio; Anastassova, Margarita (Frontiers in Mechanical Engineering, 2026)
Understanding how passengers interpret information in shared autonomous shuttles requires Human-Machine Interfaces (HMIs) that support trust, safety, and privacy across both routine and non-routine situations. This study presents an integrated evaluation of an audio-visual HMI through an online survey (N = 66) and a preliminary real-world field study (N = 12). Across both contexts, passengers preferred concise, context-dependent communication, with brief multimodal cues judged most effective for conveying upcoming manoeuvres, degraded modes, and emergency events. Transparency in vehicle-to-passenger communication, such as timely indications of system state and manoeuvre intent, was generally well received. In contrast, transparency in passenger-to-passenger visibility, such as displaying other passengers’ entry or exit locations, was rejected by both genders, although women showed stronger privacy sensitivity and greater perceived vulnerability to such exposure. Women also expressed a higher preference for discreet, non-confrontational security features. These findings demonstrate that effective HMI design for shared autonomous mobility must distinguish between system transparency and interpersonal information exposure, supporting controlled information asymmetry and privacy-protective security mechanisms. The study provides empirically grounded directions for developing inclusive and trustworthy HMIs for future autonomous public transport.